Database 'Documents of Ancient Greek Music' (dDAGM) 1.1 - Lynch, T (University of Oxford, 2021)
This database has been created by Dr Tosca A.C. Lynch (https://oxford.academia.edu/ToscaLynch) and includes all the notes attested in the ancient Greek musical documents collected in the standard edition (DAGM = Pöhlmann, E. and West, M.L., 2001, Documents of Ancient Greek Music, Oxford: OUP).